A backwater technology for enhancing pollutants discharge from aquaculture tanks in a Litopenaeus vannamei recirculating aquaculture system: Performance and control models - Jianping Xu; Yishuai Du; Jiawei Zhang; Fudi Chen; Li Zhou; Tianlong Qiu; Jianming Sun (Aquaculture Reports)
The efficient removal of the suspended solid nitrogen (SSN) from aquaculture tanks is a critical issue in a recirculating aquaculture system (RAS). In this study, a low energy consumption SSN removal technology, i.e., intermittent enhanced backwater (IEB) technology, was developed and applied to the RAS for Litopenaeus vannamei. The RAS has ten aquaculture tanks, with an total effective culture volume of 420 m3 and a stocking density of 800 shrimp/m3. Five of these aquaculture tanks were equipped with the IEB devices, while the remaining five without the IEB device. A comparison was made between the two groups to observe changes in water quality. Using IEB devices, the average total nitrogen (TN), dissolved nitrogen (DN), SSN, total ammonia nitrogen (TAN), and Vibrio concentrations in aquaculture tanks was decreased by 4.55 %, 4.45 %, 12.79 %, 10.26 %, and 10.57 %, respectively. This improvement is due to the IEB device's capability to enhance the removal of SSN, thereby minimizing its dissolution, decomposition, and mineralization. Under the action of IEB, the yield of shrimp increased by 4.48 %, with energy consumption accounting for only 0.74 % of the RAS operational energy consumption. Additionally, the relationship between the working time of the IEB device (TIEB) and the backwashing cycle of the Microscreen drum filter (TMDF) was studied, and a relevant model was established. The aim is to use TMDF feedback to control TIEB, in order to achieve automated management of the IEB device throughout the entire aquaculture process. This study provides a technical approach for optimizing the aquaculture water environment and reducing the energy consumption of RAS, and it will also promote the development of intelligence and automation in RAS.